Predictive response analysis in context of boxers` mental progress - Ivanova, L. A.; Kazakova, O. A.; Aleksin, A.Y. (Theory and Practice of Physical Culture, 2018)
The study was designed to analyze the predictive responsiveness in beginner boxers i.e. progress of their anticipative responses in the training and competitive process. This kind of analysis supported by the relevant competitive mental conditioning models may be beneficial for studies of the sport effects on the adolescents` mental progress. Good competitive progress may be secured by the training system being designed to cultivate the key qualities plus the fight techniques and tactics of importance for success. The anticipative responsiveness development element was found indispensable for progress in modern boxing as demonstrated by a training model testing experiment. Benefits of the anticipative responsiveness development tools were confirmed by a dispersion analysis, with the analytical data showing the progress of the anticipative responsiveness development efforts determined by three key factors. In terms of the practical effects of these factors, the picture is the following: the anticipative responsiveness building progress will be secured by a reasonable combination of persistent trainings and progress tests. The study data and analyses demonstrate that the choice response rate and accuracy may be fast improved in the beginner trainings conditional on a set of special anticipative responsiveness building tools being applied. The progress in this training component is determined to a lesser degree by the age-specific development rate as verified by a meaningful correlation found by the study.